Role of proapoptotic BH3‐only proteins in Listeria monocytogenes infection. Issue 6 (9th June 2016) - Margaroli, Camilla; Oberle, Susanne; Lavanchy, Christine; Scherer, Stefanie; Rosa, Muriel; Strasser, Andreas; Pellegrini, Marc; Zehn, Dietmar; Acha‐Orbea, Hans; Ehirchiou, Driss
Abstract : Here, we show that BimNoxa double knockout mice are resistant to lethal doses of Listeria . We found that they are able to clear bacterial infection more efficiently than WT mice. This effect is mainly mediated by downregulation of TNF‐α as well as increased ROS production and NET release. Abstract : The ability of pathogens to influence host cell survival is a crucial virulence factor. Listeria monocytogenes (Lm) infection is known to be associated with severe apoptosis of hepatocytes and spleen cells. This impairs host defense mechanisms and thereby facilitates the spread of intracellular pathogens. The general mechanisms of apoptosis elicited by Lm infection are understood, however, the roles of BH3‐only proteins during primary Lm infection have not been examined. To explore the roles of BH3‐only proteins in Lm‐induced apoptosis, we studied Listeria infections in mice deficient in Bim, Bid, Noxa or double deficient in BimBid or BimNoxa. We found that BimNoxa double knockout mice were highly resistant to high‐dose challenge with Listeria . Decreased bacterial burden and decreased host cell apoptosis were found in the spleens of these mice. The ability of the BH3‐deficient mice to clear bacterial infection more efficiently than WT was correlated with increased concentrations of ROS, neutrophil extracellular DNA trap release and downregulation of TNF‐α. Our data show a novel pathway of infection‐induced apoptosis that enhances our understanding of the mechanism by which BH3‐only proteins control apoptotic host cell death during Listeria infection.